Analysis of SOEs Stock Performance on the Indonesia Stock Exchange Post-Establishment of the Danantara Investment Agency - Mirna; Burhanuddin; Dasa Febriyanti (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the stock performance of BUMN (BBRI, BBNI, and BMRI) following the establishment of the Danantara Investment Agency in February 2025. Utilizing a descriptive quantitative method, this research observes stock price movements and returns during the period from February 2025 to February 2026. The results of this study indicate that the formation of Danantara triggered a volatile market reaction. There was a surge in positive returns at the beginning of its establishment (March 2025), reflecting positive market expectations aligned with the government's Signaling Theory. However, a correction phase emerged mid-year due to information asymmetry before prices eventually stabilized. Specifically, BMRI recorded the highest average price, BBRI showed the most dynamic volatility, and BBNI became the most stable issuer. The study concludes that integration into Danantara has a positive medium-term impact on the stock value of state-owned banks, supported by the fundamental strength of each bank.